Vitex doniana, In-Vitro Antioxidant, Membrane Stabilization Potential and Protective Impact Against Plasmodium berghei-Passaged Mice - Oche Okpe; Parker Elijah Joshua; Bonaventure Chinonso Obi*; Okwesilieze Fred Chitelugo Nwodo (Iranian Society of Pharmacognosy, 2023)
Background and objectives: Vitex doniana Sweet (Lamiaceae) is used to treat various ailments, including respiratory infections, liver diseases, anaemia and jaundice. This study assessed the in vitro antioxidant and membrane stabilization potential, as well as the protective impact of semi-purified solvent fractions of V. doniana leaves against Plasmodium berghei-passaged mice. Methods: Dried leaves were extracted with ethanol, followed by fractionation using a solvent-gradient system of increasing polarity (hexane, ethyl acetate, and methanol), and the concentrated fractions were obtained. Forty-two mice were randomly divided into seven groups as: group 1 (normal control), group 2 (disease control, untreated), while groups 3 to 7 received the standard drugs (artequick and chloroquine) and combined V. doniana fraction (VDF, 100 mg/kg) at varying ratios. Results: Comparatively to V. doniana extract, the fractions (F6, F8) displayed considerable antioxidant activity by scavenging O2•-, OH• and DPPH radicals, and effectively reduced Fe3+ to Fe2+. VDF (1:1) at different concentrations (200, 400, 600 µg/mL) inhibited erythrocyte haemolysis by 91.29±3.61%, 80.52±0.13%, 75.68±1.45% and 80.57±0.94%, respectively. Also, the VDF in synergy with artequick and chloroquine decreased parasitaemia levels by 4.25±0.25% and 4.65±0.28% compared to the disease control (7.93±1.61%). The combined fractions significantly normalized the plasma calcium concentration (1.85±0.17 mg/dL, 1.65±0.21 mg/dL, 1.72±0.23 mg/dL, 1.65±0.22 mg/dL) for groups 3 to 6 compared to the disease control (1.30±0.09 mg/dL), while the bodyweights presented no significant change in all experimental groups. Conclusion: The results indicate the promising potential of V. doniana as a drug candidate in managing malarial infection.